Sistem Klampid New Generation Secara Mandiri Dalam Mengentaskan Permasalahan Pengurusan Kependudukan Dan Pencatatan Sipil Surabaya - Andrew Baihaqi Firdaus; Mei Retno Adiwaty (Masyarakat Mandiri : Jurnal Pengabdian dan Pembangunan Lokal, 2024)
Surabaya, one of the major cities in Indonesia, has shown progress in the implementation of e-government, particularly in the field of population services. The Surabaya City Government has developed the Klampid New Generation application to make it easier for the community to manage population administration online. The implementation of e-government in Surabaya is based on regional regulations that provide a strong legal basis for developing digital population services. The development of the Klampid New Generation application is a manifestation of the Surabaya City Government's commitment to realizing digital transformation in the field of population administration.